Geophysical and geochemical controls on the megafaunal community of a high Arctic cold seep - Sen, Arunima; Åström, Emmelie Karin Linnea; Hong, Wei-Li; Portnov, Aleksei D; Waage, Malin; Serov, Pavel; Carroll, Michael Leslie; Carroll, JoLynn (Biogeosciences, 2018)
Source at https://doi.org/10.5194/bg-15-4533-2018 . Cold-seep megafaunal communities around gas hydrate mounds (pingos) in the western Barents Sea (76°N, 16°E, ∼ 400 m depth) were investigated with high-resolution, geographically referenced images acquired with an ROV and towed camera. Four pingos associated with seabed methane release hosted diverse biological communities of mainly nonseep (background) species including commercially important fish and crustaceans, as well as a species new to this area (the snow crab Chionoecetes opilio). We attribute the presence of most benthic community members to habitat heterogeneity and the occurrence of hard substrates (methane-derived authigenic carbonates), particularly the most abundant phyla (Cnidaria and Porifera), though food availability and exposure to a diverse microbial community is also important for certain taxa. Only one chemosynthesis-based species was confirmed, the siboglinid frenulate polychaete Oligobrachia cf. haakonmosbiensis. Overall, the pingo communities formed two distinct clusters, distinguished by the presence or absence of frenulate aggregations. Methane gas advection through sediments was low, below the single pingo that lacked frenulate aggregations, while seismic profiles indicated abundant gas-saturated sediment below the other frenulate-colonized pingos. The absence of frenulate aggregations could not be explained by sediment sulfide concentrations, despite these worms likely containing sulfide-oxidizing symbionts. We propose that high levels of seafloor methane seepage linked to subsurface gas reservoirs support an abundant and active sediment methanotrophic community that maintains high sulfide fluxes and serves as a carbon source for frenulate worms. The pingo currently lacking a large subsurface gas source and lower methane concentrations likely has lower sulfide flux rates and limited amounts of carbon, insufficient to support large populations of frenulates. Two previously undocumented behaviors were visible through the images: ...